Management of irradiated post-mastectomy wound dehiscence with synthetic electrospun fiber matrix: a case report - Montminy, Tess; Oppenheimer, Nicole E.; Cocco, Daniela (Frontiers in Oncology, 2024)
Breast-conserving surgery (BCS) is a well-established standard treatment option alternative to mastectomy for patients with early breast cancer that consists of a lumpectomy followed by adjuvant radiotherapy. However, irradiated tissues are at an increased risk of wound healing complications when post-treatment surgical management is required. The management of an irradiated wound dehiscence can be challenging, as it often requires a multimodal treatment approach that includes more invasive interventions when compared to a traditional surgical wound dehiscence. We present a 64 year old female patient with a remote history of right BCS with radiation therapy for early breast cancer 12 years ago, who recently required a simple mastectomy due to ipsilateral breast cancer recurrence. The post-operative course was complicated by dehiscence of the mastectomy wound. After standard wound care therapies failed, her surgical wound successfully healed after treatment with a synthetic electrospun fiber matrix application. Patients with additional comorbidities often do not qualify for invasive reconstructive options; therefore, effective local management options are warranted. This is the first reported case documenting synthetic electrospun fiber matrix efficacy and safety in healing a dehisced surgical wound within a previously irradiated fibrotic area, without the need for further invasive surgical intervention. Larger scale research, such as a prospective cohort study or randomized control trial, is needed to investigate its novel use in irradiated wounds.